Venture Builders and the Creation of Scaleups - Belingheri, Paola; Lechner, Christian (Springer Nature, 2025)
This open access book explores the potential of venture-builders, which is a groundbreaking model for creating startups from scratch. Unlike traditional accelerators or incubators, venture-builders leverage structured processes and expert guidance to mitigate risks and accelerate startups toward scalable growth. Providing a novel classification of venture-building models, the authors evaluate their effectiveness in fostering scaleups—high-growth firms crucial for economic development and innovation. Drawing from a unique dataset of interviews with European venture-builders, the authors go on to reveal key design archetypes and their impact on entrepreneurial ecosystems. It connects venture-building with startup scaling, addressing critical factors like access to resources, funding, and de-risking. By linking practice with research, it offers actionable insights for policymakers, academics, and practitioners. Whether you are a manager in a venture-builder, a policymaker aiming to stimulate growth, or a researcher studying entrepreneurship, this book will illuminate how venture-builders can unlock new opportunities in high-growth entrepreneurship.